Women in Trousers: Henriette d'Angeville, a French Pioneer?. (4th May 2017) - Gorguet Ballesteros, Pascale
Abstract: The story of Amelia Jenks Bloomer and her Turkish trousers figures prominently in discussions of the origins of female trousers. However, the little-known episode of Henriette d'Angeville's mountain outfit sheds new light on this history. Angeville wore trousers in 1838 to climb Mont Blanc as a sensible choice for what was a strenuous enterprise. This early example of a woman wearing trousers in a country where women had been officially forbidden to wear them since 1800 seems to have had no political dimension. D'Angeville's outfit was a practical response to the demands of physical activity rather than a political manifesto.